Awareness of patients towards eye diseases in middle aged population in rural Odisha - Rath, Bhumika; Rath, Mahesh; Mahapatra, P. C.; Sarangi, Lisa; Khan, Z. U.; Singh, Priyatama (International Journal Of Community Medicine And Public Health, 2019)
Background: One of the most important public health issue for developing nations in the world with special reference to India is preventive blindness. In the world, 36 million people are blind and 217 million people are with moderate or severe distance vision impairment. The aim and objectives of the study were a qualitative survey to get an initial picture of rural residents knowledge of the prevalent eye disease; serve as an initial assessment of patient’s baseline knowledge of eye conditions and possible treatment methods to aid in the future development of educational outreach initiatives and studies. Methods: A cross sectional study was carried out in the rural areas of Jajpur, Nayagarh, Puri and Cuttack district of Odisha during preventive eye screening camps. The study was carried over 6 months from Jan to July 2018. The sample size was calculated to be 914 and the study subjects were all aged 40 years and above comprising of 64.7% male and 35.3% female. Results: In this study we found out that 60.18% reported previous eye doctor visits, 24.08% reported using eye drops prescribed by a non-doctor, while 60.18% of the non-doctor visitors reported not knowing that a doctor should prescribe eye drops. While 76.69% had little or no awareness regarding glaucoma, 51.87% had a fair idea regarding cataract surgery. Conclusions: The increase in patient awareness of prevalent eye diseases and treatments could lead to an increase in patient acceptance regarding the importance of routine eye examinations for proper identification and treatment of various eye conditions.